[Possibilities of ACE inhibitor therapy in acute myocardial ischemia] - Ertl, G; Bauer, B; Gaudron, P; Neubauer, S; Schorb, W; Kochsiek, K (1991)
Acute myocardial ischemia results from an increased cardiac workload in presence of a critical coronary stenosis (demand ischemia), coronary occlusion (supply ischemia) or a combination of both. It is complicated by cardiac arrhythmias and deterioration of function of ischemic myocardium and results in an increased load and dilatation of non-ischemic myocardium. Cardiac protection in acute myocardial ischemia can be related to preservation of coronary blood flow, function of ischemic and non-ischemic myocardium or prevention of cardiac arrhythmias. In control animals and humans, ACE-inhibitors have no major effect on coronary blood flow. Myocardial ischemia raises plasma-renin-activity, angiotensin I-conversion by passage through coronary circulation, and plasma-angiotensin-II-concentrations. ACE-inhibitors and angiotensin-II-receptor blockers increase coronary blood flow during myocardial ischemia. Other mechanisms (bradykinin potentiation) may be involved. We found a potentiation of the coronary dilatory effect of the neuropeptide neurotensin (which is probably mediated by prostaglandins) by ACE-inhibitor. ACE-inhibitor may delay infarct development in animal experiments and improve function of ischemic myocardium. The importance of early dilatation of non-ischemic myocardium is unknown and it is unclear whether it may be prevented by an ACE-inhibitor as was shown for late dilatation. Studies on the effect of ACE-inhibitors in exercise-induced angina pectoris are controversial. An antiischemic and coronary dilatory effect has been shown by invasive studies in patients. A preliminary study in unstable angina pectoris was positive. Beneficial hemodynamic and antiarrhythmic effects (as well as excessive hypotension, however) have been shown in patients with acute myocardial infarction.